Intervención optométrica en paciente femenino de 8 años con insuficiencia de convergencia, atendido en la Óptica Richard de la ciudad de Guayaquil. - Delgado Ortiz, Richard Andrés (2025)
This case report concerns an 8-year-old patient who was diagnosed with convergence insufficiency. Convergence insufficiency is an eye problem in which the eyes cannot work together when looking at a specific object. Convergence insufficiency is a visual disorder that occurs when the nerves responsible for controlling the eye muscles don't work properly, preventing the eyes from working together to lock onto a specific object. The objective of this clinical case is to investigate the causes of convergence insufficiency and its impact on near vision in a patient. Through this study, we seek to improve the patient's visual quality, eliminating the symptoms derived from this dysfunction. In the present study, the following optometric examinations were performed, such as visual acuity (VA), X-ray, fundus, proximal point of convergence (CPP), ocular motility, cover test, among others. Among all the results obtained in the study through diagnostic examinations of this clinical case, there was convergence insufficiency, the treatment applied will be a visual therapy that has 4 phases.